Factors Influencing Consumers to Shop Online for Computer/Telecommunications Equipment - Santos, R.; Alturas, B. (ICMarkTech'21 - The 2021 International Conference on Marketing and Technologies, 2022)
The Internet has become a constant presence in citizens' lives, and this has led to great changes in what is concerned with their way to buy products. The pos-sibility of buying all the kinds of items online is particularly useful because there is no need to leave the comfort of their houses. In this study we intend to understand which are the aspects that influence the consumers to buy computer equipment and telecommunications in virtual stores. After a literature review in order to know the actual paradigm of the theme, and with the aim to deter-mine the users’ opinion, a survey was developed, which was distributed by email and within the social networks. Then the data was processed with SPSS, and it was obtained three main categories: Conditions and Image, Products and Deliveries, and finally Website design/ usability.